-12(2p-4)=3(p+12)

Simple and best practice solution for -12(2p-4)=3(p+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12(2p-4)=3(p+12) equation:


Simplifying
-12(2p + -4) = 3(p + 12)

Reorder the terms:
-12(-4 + 2p) = 3(p + 12)
(-4 * -12 + 2p * -12) = 3(p + 12)
(48 + -24p) = 3(p + 12)

Reorder the terms:
48 + -24p = 3(12 + p)
48 + -24p = (12 * 3 + p * 3)
48 + -24p = (36 + 3p)

Solving
48 + -24p = 36 + 3p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-3p' to each side of the equation.
48 + -24p + -3p = 36 + 3p + -3p

Combine like terms: -24p + -3p = -27p
48 + -27p = 36 + 3p + -3p

Combine like terms: 3p + -3p = 0
48 + -27p = 36 + 0
48 + -27p = 36

Add '-48' to each side of the equation.
48 + -48 + -27p = 36 + -48

Combine like terms: 48 + -48 = 0
0 + -27p = 36 + -48
-27p = 36 + -48

Combine like terms: 36 + -48 = -12
-27p = -12

Divide each side by '-27'.
p = 0.4444444444

Simplifying
p = 0.4444444444

See similar equations:

| log[2](5x)=k+3 | | u/3-14=19 | | 39.95+.99d=55.76 | | 3x^3+11x^2+3x=0 | | 15=u/2-8 | | 2(5x+4)-15= | | 8/3a=24 | | -1.1+x=-10.26 | | 2x-y=-3fory | | 1.1x=-1.21 | | 8(x+1)=2(2+16) | | 28+3x=6(-x+6)-62 | | -3/10x=15 | | F(t)=t-5 | | -16x=28 | | w/4=84 | | X^2=x+15 | | 55.689/57 | | 10x+-5(2x+-4)=20 | | -6.6n-4.1n=-8.56 | | 5x^3+37x^2+42x=0 | | 2.6+10m=7.29 | | -36/3 | | 12x^2+35x+12=0 | | 3=-3y+-15 | | y=3/5x=2 | | (-7x-16)/6=9 | | S/3-4=3 | | A+6-B=48 | | 6-4b=-18 | | y^2+5*y=2 | | R(x)=-0.5x^3+2.6x^2+3x |

Equations solver categories